A big drain or a river? : attachment and people's engagement - Tajuddin, Nor Azlin (2009)
Urban river pollution, generally regarded as being due to rapid urbanization, population growth, and increasing industrial activities, has received considerable attention in reports and the media in recent years. Environmental research has revealed that the Klang River in Kuala Lumpur is one the most polluted of Malaysian rivers. With a view to fulfilling a significant knowledge gap, this paper investigates the ecological values, beliefs and practices of local populations associate with this urban river. Pursuing an interest in sense of place literature, the paper discusses how local people conceptualise river pollution by highlighting the agency of the river and its water in local knowledge production.